JIWA KEWIRAUSAHAAN PELAKU AGROINDUSTRI KOPI DI KOTA BUKITTINGGI - Hariance, Rica; Putri, Afrianingsih; Nofialdi, Nofialdi (Jurnal AGRISEP, 2020)
The growing number of coffee agro-industries, the increase of consumers’ interest in coffee, and the challenges of industrial revolution 4.0, are driving demand for improving coffee agro-industry business. It encourages entrepreneurs to develop their entreprenuerial skills. This study aims to analyze the entrepreneurial spirit of the coffee agro-industry’s entrepreneur in Bukittinggi city in encountering industrial revolution 4.0. Bukittingi was selected as the study area due to leading tourist destinations in West Sumatera and its coffee agro-industry known as "Rang Bukik Apik". This research used survey method. Thirty coffee agro-industry entreprenuers were selected by simple random sampling technique. The research found that of 15 indicators assessed, the average of all indicator’s summary is 82.49%. Coffee agro-industry actor in Bukittinggi are people who are willing to take all risks, always think about goals, confident, like a challenges, like to take full outhority over themselves, optimistic, happy to immerse themselves into a work, statisfied with their product, have a high standar for the quality of work, considers of that personal and professional development is more important than senses of calm, money and prestige, likes to work hard and can combine the power of reason and intusion. To conclude, coffee agro-industry’s entrepreneurs are characterized by their high entrepreneurial spirit and capability to develop their business through product innovation and manufacturing of value-added products. At the same time, these charactiristics would be able to support entrepreneurs in facing industrial revolution era 4.0 challenges.